SECURITY IN ENERGY HARVESTING OVERLAY-BASED COGNITIVE RADIO NETWORKS - Tran Trong Hieu; Le Thanh Toi; Ho Van Khuong (HUIT Journal of Science, 2023)
This paper proposes a security solution for an energy harvesting overlay-based cognitive radio network. The solution applies artificial noise to jam the received signal at the eavesdropper. The security performance of this network is evaluated through the secrecy outage probability. Multiple results are provided to derive insights into the security of this network when artificial noise is applied, thereby determining optimum system parameters for maximum network security. Remarkably, primary/secondary communications can be secured at different levels by dynamically adjusting many system parameters of the proposed solution.